An Investigation of The Semantic Word Processing Skills of Hearing Loss and Hearing Students in Inclusive Classroom - Kargin, Tevhide; Sumer, Halime Miray; Guldenoglu, Isa Birkan (ANKARA UNIV, 2017)
It is emphasized that the studies of the hearing loss readers' word processing skills have limitations in In this study, it was aimed to compare the semantic word processing skills of hearing students, cochlear implant and hearing aids students. For this purpose, 32 hearing student and 34 hearing aid student and 35 cochlear implant student 3rd-4 th graders participated in the study. In order to examine the participants' word processing skills we used semantic word processing tests consisting of isolated written Turkish word pairs (24 related/ 24 unrelated). It has been found that hearing readers perform better than hearing aid and cochlear implant readers in terms of semantic word processing accuracy. In addition, performances of hearing aid readers and cochlear implant readers were found to perform with similar performance in terms of both response speed and error averages. When all the readers participating in the research were able to process the words in different semantic categories, it was seen that the readers processed the words with similar response speeds and error rates without depending on the semantic categories.
Keywords: Reading; reading comprehension; semantic word processing